0.3x-0.5(2x+3)=-0.8(x+2)

Simple and best practice solution for 0.3x-0.5(2x+3)=-0.8(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.3x-0.5(2x+3)=-0.8(x+2) equation:


Simplifying
0.3x + -0.5(2x + 3) = -0.8(x + 2)

Reorder the terms:
0.3x + -0.5(3 + 2x) = -0.8(x + 2)
0.3x + (3 * -0.5 + 2x * -0.5) = -0.8(x + 2)
0.3x + (-1.5 + -1x) = -0.8(x + 2)

Reorder the terms:
-1.5 + 0.3x + -1x = -0.8(x + 2)

Combine like terms: 0.3x + -1x = -0.7x
-1.5 + -0.7x = -0.8(x + 2)

Reorder the terms:
-1.5 + -0.7x = -0.8(2 + x)
-1.5 + -0.7x = (2 * -0.8 + x * -0.8)
-1.5 + -0.7x = (-1.6 + -0.8x)

Solving
-1.5 + -0.7x = -1.6 + -0.8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.8x' to each side of the equation.
-1.5 + -0.7x + 0.8x = -1.6 + -0.8x + 0.8x

Combine like terms: -0.7x + 0.8x = 0.1x
-1.5 + 0.1x = -1.6 + -0.8x + 0.8x

Combine like terms: -0.8x + 0.8x = 0.0
-1.5 + 0.1x = -1.6 + 0.0
-1.5 + 0.1x = -1.6

Add '1.5' to each side of the equation.
-1.5 + 1.5 + 0.1x = -1.6 + 1.5

Combine like terms: -1.5 + 1.5 = 0.0
0.0 + 0.1x = -1.6 + 1.5
0.1x = -1.6 + 1.5

Combine like terms: -1.6 + 1.5 = -0.1
0.1x = -0.1

Divide each side by '0.1'.
x = -1

Simplifying
x = -1

See similar equations:

| -6x=3-21 | | 29+8v=-8(v-7)+7v | | 2x-x=4x+3 | | 2(2x-3)-2(2-3x)= | | X^2-81=o | | -8(0.1x+0.4)-1.9=-0.3 | | 2y-8=8x | | 3k-2x=t-5 | | -20+4+y=-6+16 | | -1=2p | | 4n-12-7n=6-2n-9 | | 2A+3B=2C | | 8(x+2)+5=45 | | 2n-12=8n+4 | | 14x+6y=0 | | 0.8x-0.9(18-4x)=-0.7(x-6) | | 64=2t^2-8 | | 8=6y-5y+4 | | 2x+9=7x+4x | | 7d+13=35-4b | | 21=y-(-6) | | 7x-x-1=11 | | -p+6p=6+2p | | -5(1-6r)=30-5r | | 0=t-12+3 | | 14-v=16 | | (7q+3)(4q+1)=0 | | 7x+6y=-14 | | 2m=3(m-10) | | 4(y-2)=29 | | 20-z=1 | | 7=7y+2 |

Equations solver categories